2022
DOI: 10.1134/s1070328422600280
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Utility of Thiosemicarbazones with Special Reference to Mixed Ligand and Mixed Metal Complexes: A Review

Abstract: Thiosemicarbazone complexes possess structural diversity and variable bonding patterns and potential biological implications and ion sensing abilities. The ability of the transition metals to acquire different geometries like octahedral, square planar and tetrahedral in different coordination environments has encouraged researchers to explore the coordination chemistry of thiosemicarbazone complexes which can also vary upon changing aldehydes and ketones, substituents attached to the carbonyl moiety, metal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 153 publications
0
8
0
Order By: Relevance
“…Several thiosemicarbazone derivatives have biological properties either as metal complexes or as non-coordinated molecules. For examples of thiosemicarbazone complexes with biological activity, see: Gupta et al (2022); Khan et al (2022);Monsur Showkot Hossain et al (2023); Parrilha et al (2022), which covers compounds for chemotherapy and medical diagnostic imaging combined, also referred to as theranostics, and Singh et al (2023). For a review of TSC complexes in the inhibition of topoisomerases, which are biological targets of prime importance in cancer research, see: Jiang et al (2023).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Several thiosemicarbazone derivatives have biological properties either as metal complexes or as non-coordinated molecules. For examples of thiosemicarbazone complexes with biological activity, see: Gupta et al (2022); Khan et al (2022);Monsur Showkot Hossain et al (2023); Parrilha et al (2022), which covers compounds for chemotherapy and medical diagnostic imaging combined, also referred to as theranostics, and Singh et al (2023). For a review of TSC complexes in the inhibition of topoisomerases, which are biological targets of prime importance in cancer research, see: Jiang et al (2023).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Metal ions’ biological activity depends on their concentration; they can either enhance or harm the organism’s health [ 134 ]. Metal chelate has been investigated to have several biological actions, including antibacterial, anti-fungicidal, antiviral, and anti-cancer activity [ 135 , 136 ]. The biological activities of metal complexes differed from those of free ligands or metal ions, and increased or decreased activities with the non-complexed semicarbazones/thiosemicarbazones have been reported for several transition metal complexes [ 137 ].…”
Section: Application Of Thiosemicarbazone and Thiocarbazones Complexe...mentioning
confidence: 99%
“…The mixed ligand complexes have important role in biological systems as biological fluids involve mixed chelation with different ligands competing for same metal ions. Coordination of different ligands may produce synergetic effect and enhance the potential of the resulting complex [7] . A study reported Pd(II) complexes with isatin bisthiocarbohydrazone and triphenylphosphine and evaluated for their enzyme inhibitory action showing promising results [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Coordination of different ligands may produce synergetic effect and enhance the potential of the resulting complex. [7] A study reported Pd(II) complexes with isatin bisthiocarbohydrazone and triphenylphosphine and evaluated for their enzyme inhibitory action showing promising results. [8] Combined experimental and computational study of mixed ligand-metal complexes of Ni(II), Co(II), Mn(II), and Zn(II) has been reported with tenoxicam drug and valine (Val).…”
Section: Introductionmentioning
confidence: 99%